Learning to Teach: A Narrative Study of Pre-service EFL Teachers’ Experiences in the Teaching Practicum Program amidst Covid-19 Outbreak - Yuli Yana Hardiyanty; Supiani Supiani; Iwan Perdana (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
This study explores pre-service EFL teachers’ experiences in learning to teach English at the teaching practicum program during the COVID-19 Pandemic. The study adopts a qualitative narrative inquiry to capture the pre-service EFL teachers’ events or stories experienced in their learning to teach at schools. Drawing on semi-structured interview data, we found that the majority of the pre-service EFL teachers forced themselves to understand digital literacy and be able to adopt various learning platforms such as Google Classroom, Youtube, Zoom meeting, and Whatsapp in the online teaching at the practicum program during COVID-19 Pandemic. They supposed that those ways were effective enough to deliver learning materials, interact with their students and achieve learning goals. However, during online teaching at the COVID-19 Pandemic, the teaching practicum program did not run well because during the process of online teaching the pre-service EFL experienced various challenges: poor internet connection, lack their participation, and negative attitude. Therefore, the strategies they employed to overcome the teaching challenges were creating a comfortable learning atmosphere by using certain learning platforms, communicating actively with the students’ parents to encourage their online participation, and growing their self-confidence and motivation.